Rancangan Serrated Trailing Edge Propeller Unamanned Aerial Vehicle Berbahan Kayu Dan Carbon Fiber Nylon untuk Mengurangi Noise dan Dampak terhadap Thurst - Lilies Esthi Riyanti; Azzwan Tanri Pasya; Andri Kurniawan (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
Unmanned flight has been a part of everyday life. According to BI Intelegent from 2015 to 2020, the annual growth rate of small commercial UAVs is expected to reach 19%, which will result in 22 million UAV shipments by 2022. In addition, the global UAV market will reach around 10 billion USD by 2023. Problem that comes up with UAV is the propeller which based on its characteristic is a source of noise. Main noise-induced disturbance are increasing discomfort or stress, irritation, confusion, elevated blood pressure, headaches and the worst case is hearing loss. To reduce noise level caused by propeller some special treatment needed to be done to its design. The serrated trailing edge theory was first introduced by M.S. Howe and then developed by applying the serrated trailing edge to the propeller by Zhe Ning, Richard Wlezien, Hui Hu. The journal concluded that the serrated trailing edge can reduce noise up to 1.6dB. In this study, the author makes a propeller design with a serrated trailing edge using the Solidwork application. After making the design, proceed to the process of making the propeller, after being made it enters the testing stage using the Sunnysky X-2820 motor testing tool on 3000, 4000, 5000 RPM and noise is measured with a sound level meter with several differences in distance, namely 1m, 1.5m, 3m to determine the noise and thrust generated by each propeller.